Nutrition and chronic kidney disease (CKD): Presentation of new recommendations and food standards by the last scientific evidence (Research, Society and Development, 2021)
Chronic kidney disease (CKD) is a slow, silent, irreversible and progressive syndrome of kidney function and, thus, nutritional management remains among the most important interventions to slow the progression of CKD. This is a systematic review, carried out on the databases: LILACS, SciELO and ScienceDirect, based on the following descriptors: Nutrition, Chronic Kidney Disease, Food Pattern and Diet, in which the Boolean operators “AND” and “OR” were used, carrying out the different combinations. The corpus of this investigation comprised 18 scientific articles, including two guidelines published in the last five years. In order to systematically present the evidence gathered around the new nutrition and CKD recommendations, five tables were prepared containing information about publications, stages of kidney disease, protein recommendations in conservative treatment and in renal replacement therapy, carbohydrates, lipids and energy in both modalities. It is identified that the evidence regarding a dietary pattern is still quite controversial, however the literature shows that the dietary pattern with a focus on foods of plant origin, fruits, whole grains, legumes, rich in fiber and moderate consumption of foods animal origin, promote beneficial effects in the management and prevention of metabolic complications of CKD. Therefore, to date, there is no specific standard for controlling nephropathy disorders, since dietary control goes from the individuality of each patient and the investigative-critical analysis of the nutritionist.